Stabilization of the spectral-element method in turbulent flow simulations - Ohlsson, J.; Schlatter, Philipp; Fischer, P. F.; Henningson, D. S. (Lecture Notes in Computational Science and Engineering, 2011)
The effect of over-integration and filter-based stabilization in the spectral-element method is investigated. There is a need to stabilize the SEM for flow problems involving non-smooth solutions, e.g., turbulent flow simulations. In model problems such as the Burgers' equation (similar to Kirby and Karniadakis, J. Comput. Phys. 191:249-264, 2003) and the scalar transport equation together with full Navier-Stokes simulations it is noticed that over-integration with the full 3/2-rule is not required for stability. The first additional over-integration nodes are the most efficient to remove aliasing errors. Alternatively, filter-based stabilization can in many cases alone help to stabilize the computation. © 2011 Springer.
CRIS-Team Scopus Importer:2023-03-21